Nutrition Guide for Physicians - Wilson, Ted.; Bray, George A.; Temple, Norman J.; Struble, Maria Boyle; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2010)
Nutrition Guide for Physicians is a desktop reference guide on nutrition and its clinical implications for health and disease through the lifecycle. Presented in a new softcover format and user-friendly style, it serves as a valuable resource of practical information on nutrition for physicians in their daily practice. Nutrition Guide for Physicians is divided into three parts that cross the spectrum of nutritional concerns for improving the practice of medicine. Part One provides basic nutritional principles for physicians. Part Two covers nutrition through the lifecycle and optimal nutrition patterns through all stages of development. Part Three covers diet and its role in prevention, cause and treatment of disease. All chapters include figures and tables that provide useful descriptive and visual reviews. "Key points" and succinct "conclusions" are also provided for each topic. Nutrition Guide for Physicians provides a wide perspective of the impact that nutrition has upon medical practice and will be am indispensable resource for primary care physicians and other medical professionals.
Fat: The Good, the Bad, and the Ugly -- Dietary Fiber: All Fibers are not Alike -- Sugar and Artificial Sweeteners: Seeking the Sweet Truth -- Vitamins and Minerals: How much do we Really Need?- Dietary Reference Intakes: Cutting through the Confusion -- Food Labels and Sources of Nutrients: Sorting the Wheat from the Chaff -- Vegetarian and Vegan Diets: Weighing the Claims -- Dietary Recommendations for Non-Alcoholic Beverages -- Should Moderate Alcohol Consumption be Promoted?- Issues of Food Safety: Are "Organic" Apples Better?- What is a Healthy Diet? From Nutritional Science to Food Guides -- Achieving Dietary Change: The Role of the Physician -- Dietary Supplements: Navigating a Minefield -- Taste Sensation: Why we eat what tastes good -- Pregnancy: Preparation for the Next Generation -- Infants: Transition from Breast to Bottle to Solids -- Young Children: Preparing for the Future -- Adolescents and Young Adults: Facing the Challenges -- Healthy Aging: Nutrition Concepts for Older Adults -- Assessing Nutritional Status: How Do We Know If Our Diet Is Healthy?- Eating Disorders: Disorders of Under- and Over-nutrition -- Obesity: Understanding and Achieving a Healthy Weight -- Nutrition Therapy Effectiveness for the Treatment of Type 1 and Type 2 Diabetes: Prioritizing Recommendations Based on Evidence -- Diabetes: Lifestyle Interventions to Stem the Tide of Type 2 Diabetes -- Coronary Heart Disease: Nutritional Interventions for Prevention and Therapy -- Diet and Blood Pressure: The High and Low of It -- Gastrointestinal Disorders: Does Nutrition Control the Disease?- Nutrition in Patients with Diseases of the Liver and Pancreas -- Medical Nutrition Therapy in Chronic Kidney Disease and Other Disorders -- Bone Health: Sound Suggestions for Stronger Bones -- Inherited Metabolic Disorders and Nutritional Genomics: Choosing the Wrong Parents -- Nutritional Challenges of Girls and Women -- Diet, Physical Activity, and Cancer Prevention -- Food Allergy and Intolerance: Diagnoses and Nutritional Management -- Drug Interactions with Food and Beverages -- Appendices -- Aids to Calculations -- Sources of Reliable Information on Nutrition -- Dietary Reference Intakes (DRI) Tables.
Keywords: Medicine; Nutrition; Family medicine; Personal health and hygiene; Emergency medicine; Medicine & Public Health; Clinical Nutrition; Nutrition; Primary Care Medicine; General Practice / Family Medicine; Health Promotion and Disease Prevention